Jenis-jenis Trikoma pada Tumbuhan Solanaceae, Malvaceae dan Asteraceae sebagai Sumber Bahan Praktikum pada Materi Anatomi Tumbuhan - Ayub, Nurfitrah Aulia; Karim, Hilda; Syamsiah, Syamsiah (Universitas Negeri Makassar, 2021)
Abstract. This research is exploratory descriptive which aims to explore knowledge for the introduction and understanding of a phenomenon whose information is still lacking. The subjects of this study were plants from the Solanaceae, Malvaceae and Asteraceae tribes which were considered cosmopolitan. Research activities carried out through three stages, namely the preparation phase, the implementation phase and the final stage. In the preparation stage, research tools and materials are provided. The implementation stage is the observation of trichomes in plant specimens using a digital monopod microscope. In the final stage, identification of the types of trichomes possessed by the research materials and the preparation of trichome practicum guides in dicotyledonous plants based on the work steps carried out during the study. Based on observations there are 12 types of plants from the Solanaceae, Malvaceae and Asteraceae tribes which can be recommended as ingredients for the practice of trichome in plant anatomy material.Keywords: guide, trichome, exploration, practicum.